Model społecznej gospodarki rynkowej w ujęciu Wincentego Stysia - Kowalczyk, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The paper presents basic elements of the economic and social conception framed by Wincenty Styś. A special attention has been paid to the notion of political democracy and socio-economic system, which have been presented against the background of the Polish and world economic thought. The author of the article has discussed Styś’s views on the problem of functioning of state in economic life. In the final remarks, the importance of Styś theory has been analyssed in relation to the modern economics
Keywords: Styś, Wincenty (1903-1960); gospodarka rynkowa